Error Analysis of Using Simple Present Tense on Students’ Descriptive Text Writing - Susiana Pancawati; Nina Dwiastuty (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2021)
The purpose of the research is to find out the types of error which made by the ninth graders in writing descriptive text using simple present tense at SMPIT Nurul Ihsan. The number of the students is 27 students. This research uses qualitative descriptive as the approach. The researcher directly did the survey and conducted a written test to the students write English descriptive text. The result of the study shows that there are 77 errors from all students’ compositions. The most error made is misformation with the percentage 49,35%. Followed misordering with the percentage 20,78%, then addition with the percentage 18,18%, and the least error made is omission with the percentage is 11,69%. Most students made wrong sentence in misformation category. The cause of that is the interference from mother language or L1. It makes them influenced the way they think about the language they are learning. When they compose a text in English, they follow the rule of L2. Consequently, they should be guided more so that they could understand about simple present tense.